2017
DOI: 10.1016/j.stem.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Platform for Differentiation of Human PSCs into All Major Ectodermal Lineages

Abstract: SUMMARY Directing the fate of human pluripotent stem cells (hPSCs) into different lineages requires variable starting conditions and components with undefined activities, introducing inconsistencies that confound reproducibility and assessment of specific perturbations. Here we introduce a simple, modular protocol for deriving the four main ectodermal lineages from hPSCs. By precisely varying FGF, BMP, WNT, and TGFβ pathway activity in a minimal, chemically-defined medium, we show parallel, robust, and reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
183
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(199 citation statements)
references
References 36 publications
4
183
0
Order By: Relevance
“…To model both the central nervous system and mesenchymal manifestations that develop in TSC, we conceived parallel lineage induction approaches to generate cultures enriched for neural precursor cells (NPCs) or mesenchymal-like neural crest cells (NCCs) based on small molecule dual SMAD signaling inhibition (dSMADi) of hPSCs ( Figure 1A, 1G). dSMADi promotes rapid exit from pluripotency and induction of a predominant dorsal neuroectoderm (NE) fate, with consequent potential to promote enrichment of NE-derived NPCs or NCCs by defined culture conditions (Chambers et al, 2009;Tchieu et al, 2017). Validating previous findings and our rationale, RNA sequencing (RNA-seq) of end-point cultures revealed that dSMADi of high density adherent monolayer hPSCs resulted in a dominant NPC gene signature ( Figure 1G, S1D); conversely, an embryoid body (EB) induction approach permitted NCC marker gene enrichment ( Figure 1G, S1D).…”
Section: Generation Of a Tsc2 -/-Hpsc Library Using Crispr/cas9mentioning
confidence: 99%
See 1 more Smart Citation
“…To model both the central nervous system and mesenchymal manifestations that develop in TSC, we conceived parallel lineage induction approaches to generate cultures enriched for neural precursor cells (NPCs) or mesenchymal-like neural crest cells (NCCs) based on small molecule dual SMAD signaling inhibition (dSMADi) of hPSCs ( Figure 1A, 1G). dSMADi promotes rapid exit from pluripotency and induction of a predominant dorsal neuroectoderm (NE) fate, with consequent potential to promote enrichment of NE-derived NPCs or NCCs by defined culture conditions (Chambers et al, 2009;Tchieu et al, 2017). Validating previous findings and our rationale, RNA sequencing (RNA-seq) of end-point cultures revealed that dSMADi of high density adherent monolayer hPSCs resulted in a dominant NPC gene signature ( Figure 1G, S1D); conversely, an embryoid body (EB) induction approach permitted NCC marker gene enrichment ( Figure 1G, S1D).…”
Section: Generation Of a Tsc2 -/-Hpsc Library Using Crispr/cas9mentioning
confidence: 99%
“…hPSCs were passaged as intact colonies, maintained on Matrigel, and neural lineage differentiation was initiated when the cultures were 90%+ confluent to promote neuroepithelial induction (Tchieu et al, 2017), typically 3-5 days post-passage. Neuroectoderm differentiation was initiated by replacing E8 with KSR media containing 10µM SB and 500nM LDN.…”
Section: Monolayer-npc Differentiationmentioning
confidence: 99%
“…Cells in the SOX2 high POU5F1 low Ectoderm cluster express neuroectoderm markers, NES (Lendahl, Zimmerman and McKay, 1990), VIM (Schnitzer, Franke and Schachner, 1981), DLK1 (Surmacz et al, 2012), and LGI1 (Tchieu et al, 2017). We also detected transcripts expressed in mouse ectodermal derivatives, DLX5, CYFIP2, PTN, GLI3, ID3, CRABP2, and SFRP1 (Pijuan-Sala et al, 2019) (Figure 2C).…”
Section: Ectodermal Cluster Expressing Nonneural and Neural Ectoderm mentioning
confidence: 76%
“…While sample sizes in these iPSC studies tend to be small (ranging from 3 in Deshpande et al, 2017 to 8 autistic subjects with macrocephaly in Marchetto et al, 2017 andSchafer et al, 2019), these studies nonetheless highlight that iPSCs can be used to model brain overgrowth in autism and gain insight on underlying mechanisms. To begin to model gray matter using human iPSCs, we differentiated the iPSCs into NPCs using an established NPC differentiation protocol that gives rise to cortical neurons 29,30 . Following 12 days of directed differentiation ( Figure 1C), NPCs express Pax6 mRNA at comparable and high levels of >1000-fold relative to undifferentiated iPSCs ( Figure 1D).…”
Section: Upregulation Of Cd47 In 16p112 Deletion Npcs Suppresses Phamentioning
confidence: 99%
“…Control and 16p11.2 CNV iPSCs were differentiated into cortical neural progenitor cells (NPCs) as previously described 29,30 . The iPSC cultures were plated at a high-density monolayer onto GelTrex (ThermoFisher) coated wells.…”
Section: Generation Of Neural Progenitor Cells (Npcs)mentioning
confidence: 99%